Gawa’ Tradition in Inter-Tribal Marriages in Mentebah, Kapuas Hulu, West Kalimantan: Acculturation, Function, and Humanity - Muhammad Fadhly Akbar (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2023)
Local customs influence many Islamic wedding practices in Indonesia. However, not all practices effectively maintain community harmony. This article explores how the Malay and Dayak Mentebah tribes negotiate and position the Gawa' tradition within the societal realm. Employing a socio-anthropological approach, this article finds that the Gawa' tradition is carried out in two forms: one based on Islamic legal norms practiced by the Malay community and the other based on customary norms observed by the Dayak Mentebah community, even if the bride or groom has converted to Islam. Cultural negotiation occurs in several acculturated aspects, from wedding decorations, bridal attire, food composition, and musical instruments to entertain guests. Although some aspects may violate Islamic legal principles, such as serving pork and alcoholic drinks, the tradition significantly impacts individuals, families, and the community by creating a harmonious and mutually beneficial interaction space for both tribes. Regardless of the Malay and Dayak Mentebah tribe's view of Gawa' as a mandatory cultural norm that upholds personal, familial, and communal dignity, they have approached this tradition with humanity and deep respect for each other's beliefs, avoiding large-scale social conflict. Instead, Gawa' serves as a space that fosters social strength grounded in multiculturalism.